Adsorção de íons mercúrio em uma rede de poli(dimetilsiloxano) funcionalizada com tiol contendo nanopartículas de prata - Ferrarezi, Lucas (2019)
Considering the variety of matrixes uses constituted by poly(dimethylsiloxane)(PDMS), this work synthetized a polymeric network functionalized with thiol or sulfonic groups containing silver nanoparticles. The produced materials were characterized by the Thermogravimetric Analisys (TGA), showing thermal stability until 210ºC. Amongst the synthetized and researched materials, the one containing dibutyltin dilaurate and silver nanoparticles exhibited higher thermal stability. Diferential Scanning Calorimetry (DSC) showed the formation of a poly(dimethylsiloxane) network without modification of the PDMS chain dimension Fourier-Transform Infrared (FTIR) showed that the material functionalization was efficient and Scanning Electron Microscopy (SEM) indicated an increase on the contact area of the materials with the insertion of the silver nanoparticles. The adsorption potential for mercury ions in aqueous solutions, for the polymeric networks, was obtained by adsorption isotherms. Was applied the Langmuir, Freundlich and Sips models in the adsorption data. The sulfonated polymeric network containing silver nanoparticles presented as the most promising adsorbent for mercury ions in aqueous solutions.